Perancangan Kampanye Cara Pintar dalam Berhemat Listrik Prabayar - Setyo, Sutikno Try; Iswandi, Heri; Yulius, Yosef (Besaung : Jurnal Seni Desain dan Budaya)
Government innovation by presenting prepaid electricity services or better known as "smart electricity" with the aim of improving service to the community. PLN introduces prepaid electricity services that can regulate and check electricity usage alone, but some people are reluctant to use prepaid electricity because it is considered more wasteful and more expensive than electricity with a postpaid payment system.The design of the Smart Way to Save Electricity Prepaid Campaign aims to invite the community and change the negative stigma that exists in the community about prepaid electricity itself. The results of this design turned out that when the design of this campaign was exhibited to the public, not a few people responded, even many of them only knew using or consuming it, without thinking about savings. From these results it can be concluded that the campaign and socialization of energy savings were very important and responded positively by the community.